2004
DOI: 10.1080/09528130412331294715
|View full text |Cite
|
Sign up to set email alerts
|

Making meaning happen

Abstract: What is it for a sound or gesture to have a meaning, and how does it come to have one? In this paper, a range of simulations are used to extend the tradition of theories of meaning as use. The authors work throughout with large spatialized arrays of sessile individuals in an environment of wandering food sources and predators. Individuals gain points by feeding and lose points when they are hit by a predator and are not hiding. They can also make sounds heard by immediate neighbours in the array, and can respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…For more on the relationship between animal signals and mentalistic language see Radner (1999). 7 For an analysis of signaling games which include the realistic feature of local interaction see Grim et al (2001) and Zollman (2005). 8 On this view, one may wonder about the status of a cry for help like 'Help!'.…”
Section: Normative and Descriptive Statementsmentioning
confidence: 99%
“…For more on the relationship between animal signals and mentalistic language see Radner (1999). 7 For an analysis of signaling games which include the realistic feature of local interaction see Grim et al (2001) and Zollman (2005). 8 On this view, one may wonder about the status of a cry for help like 'Help!'.…”
Section: Normative and Descriptive Statementsmentioning
confidence: 99%
“…In more recent models, our individuals instantiate simple neural nets, doing a partial training on the behavior of successful neighbors [3], [4].…”
Section: Semantic Content and Pragmatic Convention: Emergence Throughmentioning
confidence: 99%
“…The internal states of the AA are excellent candidates for the role of nonsemantic yet semantic-inducing resources." Indeed, in an earlier study, Grim showed that signs can acquire meanings by coordinating signaling across artificial creatures in an agent-based model [19]. "Truth telling," here, emerged even in elementary models based solely on the interaction between agents, agent-environment relations, and simple mechanisms internal to each agent.…”
Section: Framing the Question Along Informationtheoretic Linesmentioning
confidence: 99%
“…However, action-based semantics may provide another alternative. (See, for instance, [18] and [19].) Respecting the former, Floridi notes, "in the beginning, the proto-meanings of the symbols generated by an AA [artificial agent] are the internal states of that AA, which in turn are directly correlated to the action performed by the same AA" (p. 164 [18]).…”
Section: Framing the Question Along Informationtheoretic Linesmentioning
confidence: 99%
See 1 more Smart Citation